Significant excess of early deaths after prehospital ticagrelor: The ATLANTIC trial challenge - Serebruany, Victor; Cherepanov, Vasily; Dukhanin, Alexander (Thrombosis and Haemostasis, 2015)
The recently published Administration of Ticagrelor in the Cath Lab or in the Ambulance for New ST Elevation Myocardial Infarction to Open the Coronary Artery (ATLANTIC) trial concluded that prehospital administration of ticagrelor in patients with acute STEMI appeared to be safe but did not improve pre-PCI coronary reperfusion. The ATLANTIC data fully support the PLATO Angiographic Substudy denying early benefit of ticagrelor, and correspond well with lack of immediate clinical benefit including the early PCI “death paradox„ in PLATO-USA patients. Finally, there were significantly (p=0.043) more deaths in early ticagrelor ATLANTIC arm (odds ratio 3.18 (1.02–9.90) challenging stent thrombosis reduction. Indeed, ATLANTIC represents an important step for our better understanding of ticagrelor, although the confirmation of the PLATO mortality wonder in an adequately powered PEGASUS (TIMI-54) to be reported in 2015 will be vital for ticagrelor future.